A review of pediatric neuroendocrine tumors, their detection, and treatment by radioisotopes. Issue 1 (January 2021) - Haddad, Tara; Fard-Esfahani, Armaghan; Vali, Reza
Abstract : Neuroendocrine tumors (NETs) are rare in childhood. Neuroblastoma is the most common pediatric extracranial solid tumor, occurring >90% in children younger than 5 years of age. Pheochromocytoma and paraganglioma are rare NETs, causing hypertension in 0.5–2% of hypertensive children. Gastroenteropancreatic NETs can occur in children and are classified into carcinoids and pancreatic tumors. Nuclear medicine procedures have an essential role both in the diagnosis and treatment of NETs. Metaiodobenzylguanidine (MIBG) labeled with radioiodine has a well-established role in diagnosis as well as therapeutic management of the neuroblastoma group of diseases. During recent decades, establishing the abundant expression of somatostatin receptors by NETs first led to scintigraphy with somatostatin analogs (i.e. 99m Tc/ 111 In-octreotide) and, later, with the emergence of positron-emitting labeled agents (i.e. 68 Ga-DOTATATE/DOTATOC/DOTANOC) PET scans with significantly higher detection efficiency became available. Therapy with somatostatin analogs labeled with beta emitters such as Lu-177 and Y-90, known as peptide receptor radionuclide therapy, is a promising new option in the management of patients with inoperable or metastasized NETs. In this article, pediatric NETs are briefly reviewed and the role of radioactive agents in the detection and treatment of these tumors is discussed.